LOGISTIC APPROACH IN CREATING AN EFFECTIVE MECHANISM OF PASSENGER TRANSPORTATION MANAGEMENT BY RAILWAY TRANSPORT - V. I. Kopytko (Nauka ta progres transportu, 2009)
The logical concept of passenger transportation management on the railway transport is considered. This concept provides the creation of logical centers, which must combine the market mechanism with the government regulation. It is motivated that the efficient work condition of logical centers is a determination of main factors, due to which it is possible to realize the classification of passenger traffic that will allow forecasting the behavior of a logistic structure at the passenger market.